Health promotion through movement: Examining the correlation between lower extremity flexibility, balance, and demographic factors - Utomo Wicaksono; Bernadus Sadu; Ermeisi Er Unja; Dadan Prayogo; Aulia Rachman; Imelda Ingir Ladjar (Journal of Education and Health Promotion)
Background: Healthy aging is a critical aspect of overall health, and maintaining physical function is essential for independence and quality of life. Lower extremity flexibility and balance are vital components of physical function, and demographic factors such as age, gender, and body mass index (BMI) can impact these factors. This study aims to examine the relationship between lower extremity flexibility, balance, and demographic factors to promote healthy aging. Materials and Methods: This analytic observational study used a cross-sectional approach. Lower extremity flexibility was measured using the Sit and Reach Test (SRT), balance ability was assessed using the Functional Reach Test (FRT), and demographic factors were collected through self-report. Results: The study found significant relationships between: - Age and balance ability (P = 0.01 < 0.05), with an odds ratio (OR) of 9.72 (2.97–31.79) - BMI and balance ability (P = 0.01 < 0.05), with an OR of 3.92 (1.30–11.84) - Lower extremity flexibility and balance ability (P = 0.03 < 0.05), with an OR of 3.29 (1.12–9.65). However, when adjusted for older age and higher BMI, lower extremity flexibility was not significantly associated with balance ability (P = 0.66 > 0.05 and P = 1.00 > 0.05, respectively). Conclusion: Promoting healthy aging requires consideration of lower extremity flexibility, balance, and demographic factors. This study highlights the importance of maintaining flexibility and balance, particularly in older adults and those with higher BMI. Healthcare professionals can use these findings to develop targeted interventions promoting healthy aging.